Barriers and enablers to primary health care center access for older people in Lebanon: A qualitative inquiry - Saydeh Dableh; Kate Frazer; Mathilde Azar; Randa Hamadeh; Thilo Kroll (PLoS ONE, 2025)
Introduction Older people in low- and middle-income countries face significant challenges when accessing primary care services. In Lebanon, most older people (75%) living with at least one chronic disease previously accessed private health services for care. However, the economic crisis substantially increased their reliance on primary healthcare centers (PHCCs), while factors shaping access to public services were unknown. This study explores the barriers and enablers influencing access to PHCCs’ services. Methods This descriptive qualitative study involved 57 people including older adults (aged 60–92 years), informal caregivers, and service providers, recruited using maximum variation sampling. Data were collected through seven focus groups and fifteen interviews. The Framework Method was adopted for thematic analysis. The Patient-centered Access to Healthcare Framework facilitated mapping of barriers and enablers across five access opportunities. Results Findings are presented under five themes: 1) perception of healthcare needs , enabled by acute symptoms, free services, literacy, and familial support but hindered by lack of information on services; 2) healthcare seeking , supported by respectful providers, familial support, available quality services, and positive leadership, but constrained by providers’ attitudes, poor service organization, limited finances, and negative perceptions; 3) healthcare reaching , enabled by proximity of PHCCs and home care, but limited by transport issues, mobility restrictions, staff and resource shortages, and service delivery challenges; 4) healthcare utilization , facilitated by low fees and economic recession, but hindered by lack of funds and financial resources; and 5) healthcare consequences, facilitated through positive relationships, literacy, and personal abilities, but constrained by cognitive and sensory limitations, poor relationships, and lack of care continuity, coordination, comprehensiveness, and patient-centeredness. Conclusions This study highlights the challenges for older people, indicating factors to be strengthened and barriers requiring action at the PHCC and multi-sectoral levels. Ensuring adequate funding, information, and health coverage is primordial to improve older people’s access to PHCCs.